Rabbit Antithymocyte Globulin Causes Blastomyces and Histoplasma Antigenemia - Kaur, Amrit (Open Forum Infect Dis, 2019)
Rabbit antithymocyte globulin (rATG) is known to yield false-positive Histoplasma antigenemia. The fourth generation MiraVista Histoplasma antigen assay was modified to block this effect (MiraVista Diagnostics, Indianapolis, Indiana). We report a case of rATG-induced false-positive Blastomyces and Histoplasma antigenemia in a lung transplant recipient despite modifications of these antigen assays.